Pelatihan Penguatan Kemampuan Numerasi Domain Aljabar pada Guru SD - Seftyana Ayu Susanti (Jurnal Pengabdian Pendidikan, 2025)
Numeracy is an important skill that students must have to a meaningful life. Numeracy is defined as the ability to process, communicate, and interpret numerical information in various contexts that involve the use of mathematical concepts to achieve several goals in certain contexts in everyday life problems. One of the domains in numeracy assessment is algebra. Algebra is a branch of mathematics that uses symbols (variables) and operating rules to manipulate mathematical expressions and solve equations. Algebra is a material that many students dislike because of its complexity. The importance of algebra in learning mathematics requires students to study it from elementary school and continue to higher education with a more complex level of difficulty. For this reason, it is important for elementary school teachers to have algebraic domain numeracy skills in order to be able to maximally accompany students in their learning. So that this training aims to provide reinforcement of algebraic domain numeracy skills both in terms of understanding the theory and compiling AKM model questions for elementary school teachers as provisions in teaching it to students. Numerasi adalah kemampuan penting yang harus dimiliki oleh siswa untuk mendapatkan kehidupan yang bermakna. Numerasi didefinisikan sebagai kemampuan untuk memproses, berkomunikasi, dan menafsirkan informasi numerik dalam berbagai konteks yang melibatkan penggunaan konsep matematika untuk mencapai beberapa tujuan dalam konteks tertentu dalam permasalahan di kehidupan sehari-hari. Salah satu domain dalam penilaian numerasi adalah aljabar. Aljabar merupakan cabang matematika yang menggunakan simbol (variabel) dan aturan operasi untuk memanipulasi ekspresi matematika dan menyelesaikan persamaan. Aljabar menjadi materi yang banyak tidak disukai oleh siswa karena kerumitannya. Pentingnya aljabar dalam pembelajaran matematika mengharuskan siswa mempelajarinya sejak bangku sekolah dasar dan terus berlanjut hingga pendidikan yang lebih tinggi dengan tingkat kesulitan yang lebih kompleks. Untuk itu, penting bagi guru SD memiliki kemampuan numerasi domain aljabar agar dapat secara maksimal membersamai siswa dalam belajarnya. Sehingga adanya pelatihan ini bertujuan untuk memberikan penguatan kemampuan numerasi domain aljabar baik secara pemahaman teori hingga penyusunan soal-soal model AKM pada guru SD sebagai bekal dalam mengajarkannya kepada siswa.